Penerapan Model Pembelajaran Children Learning In Science Untuk Meningkatkan Proses, Motivasi dan Hasil Belajar Pada Pembelajaran IPAS Kelas IV SDN 112/II Purwobakti - Nesa Desmawita; Sundahry Sundahry; Reni Guswita (Master of Pedagogy and Elementary School Learning, 2026)
This study is driven by the observation that learners tend to be somewhat inactive during the educational experience in classrooms, coupled with a deficiency in an interactive learning approach, which leads to diminished enthusiasm and academic performance in science. The objective of this research is to illustrate advancements in the engagement, motivation, and intellectual achievements of fourthgrade pupils at SDN 112/II Purwobakti. This investigation takes the form of classroom action research. The participants included 11 fourthgrade learners from SDN 112/II Purwobakti. The methodology comprised four phases: planning, implementation, monitoring, and evaluation. The research unfolded over two cycles, each consisting of two sessions. Data gathering methods involved observation, a motivation questionnaire, and assessments. The findings reveal that the Children Learning in Science model can enhance the engagement, motivation, and academic results of fourthgrade learners at SDN 112/II Purwobakti. This enhancement was noticeable from teacher evaluations in the first cycle, averaging 57%, and in the second cycle, reaching 78.5%. Student assessment results in cycle I showed 58.5%, while in cycle II, it rose to 72%. Student motivation in cycle I was recorded at 54.54%, which increased to 72.72% in cycle II. In cycle I, 54.54% of students met the KKTP (minimum competitive standard). Additionally, in cycle II, this figure grew to 81.81% of students reaching the KKTP, with a KKTP threshold of 70. Thus, it can be concluded that employing the Children Learning in Science model effectively boosts student motivation and academic performance in science classes for fourth graders at SDN 112/II Purwobakti